Upper Lip Asymmetry During Smiling: An Analysis Using Three-Dimensional Images - Andrew Mathis; Daniel M. Laskin; Eser Tüfekçi; Caroline Caricco; Steven J. Lindauer (Galenos Yayinevi, 2018)
Objective:The aim of this study was to use three-dimensional images to determine the presence of upper lip asymmetry at rest and during smiling in a group of individuals with no history of orthodontics or facial cosmetic surgery.MethodsStandardized three-dimensional frontal resting and smiling images of 54 volunteers were analyzed using the 3dMDvultus software (3dMD, Atlanta, GA). Measurements were made from the soft tissue nasion, ipsilateral ala, subnasale, and menton to the right and left commissures of the lip. A 2.5 mm or greater difference between the right and left sides was defined as an asymmetry. The agreement on the presence or absence of asymmetry between the subjects' states of rest and smiling was determined by the McNemar's chi-squared test. Statistical significance was defined as p<0.05.Results:Menton was the most stable facial landmark to evaluate the upper lip symmetry at rest and during smiling (p=0.002). Using menton as a landmark, only one of the 54 subjects showed asymmetry while resting, but 12 (22%) showed asymmetry when smiling.Conclusion:As part of treatment planning for orthodontics or orthognathic surgery, patients should be evaluated for the upper lip symmetry during resting and smiling. The presence of asymmetry during smiling is a significant clinical problem that needs to be recognized so that patients can be informed about the effect it can have on the final esthetic result.